1999
DOI: 10.1046/j.1365-2168.1999.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized trial of end-to-end versus side-to-side biliary reconstruction after orthotopic liver transplantation

Abstract: Side-to-side and end-to-end biliary anastomosis at liver transplantation are equally effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 22 publications
2
49
0
4
Order By: Relevance
“…In addition, a good perfusion of the bile duct is warranted, since the 3 and 9 o'clock vessels are completely preserved by incision of the bile duct at 12 and 6 o'clock ( Figure 2). However, a randomized trial comparing these technical modifications showed no significant differences (35). Overall, no differences between running and interrupted sutures have been detected (19,36), but there is some indication for less AS with interrupted sutures (5.1% vs. 9.8%) (36).…”
Section: Prophylaxis Of Anastomotic Complicationsmentioning
confidence: 92%
“…In addition, a good perfusion of the bile duct is warranted, since the 3 and 9 o'clock vessels are completely preserved by incision of the bile duct at 12 and 6 o'clock ( Figure 2). However, a randomized trial comparing these technical modifications showed no significant differences (35). Overall, no differences between running and interrupted sutures have been detected (19,36), but there is some indication for less AS with interrupted sutures (5.1% vs. 9.8%) (36).…”
Section: Prophylaxis Of Anastomotic Complicationsmentioning
confidence: 92%
“…With improvements in organ selection, retrieval, preservation, and implantation techniques such complications have been reduced dramatically. Biliary complications, however, still occur in 10–30% following whole-organ OLT resulting in mortality rates up to 10% of cases [5,6,7,8,9,10,11] (table 1). …”
Section: Introductionmentioning
confidence: 99%
“…The end-to-end or side-to-side choledochocholedochostomy (CCS) reconstruction program for OLT has been accepted by most transplant centers (Davidson et al, 1999;Castaldo et al, 2007). The T-tube is widely used in CCS as a stent of the biliary tract, for it can not only protect against anastomotic strictures, but also help to monitor the flow and color of bile, and makes it easy to perform cholangiography when necessary (Lerut et al, 1987;Shaked, 1997;de Simone et al, 2005).…”
Section: Introductionmentioning
confidence: 99%